Myocardial injury biomarkers after radiofrequency catheter and cryoballoon ablation for atrial fibrillation and their impact on recurrence - Kızılırmak, Filiz; Gökdeniz, Tayyar; Güneş, Hacı Murat; Demir, Gültekin Günhan; Çakal, Beytullah; Babur Güler, Gamze; Güler, Ekrem; Olgun, Fatih Erkam; Kılıçaslan, Fethi (Via Medica, 2017)
Background: Myocardial injury induced by catheter ablation (CA) for atrial fibrillation (AF) leads to elevated biomarker levels. Aim: This prospective study examined levels of myocardial injury biomarkers (creatinine kinase [CK], myocardial bound for CK [CK-MB], and troponin I [TnI]) and their impact on AF recurrence following two different ablation strategies, namely: cryoballoon ablation (CBA) and radiofrequency ablation (RFA). We also aimed to evaluate the relationship between AF recurrence after CA and other clinical, echocardiographic and procedural parameters. Methods: We enrolled 98 patients with AF, 21% of whom had persistent AF and 79% had paroxysmal AF. 58% of patients underwent CBA, and 42% underwent RFA. CK, CK-MB, and TnI levels were measured before and 6 h after the procedure. Patients had follow-up visits three, six, and nine months after the index procedure. Biomarker levels were compared between the patients with and without AF recurrence. Results: Post-ablation CK (postCK), post-ablation CK-MB (postCKMB), and post-ablation TnI (postTnI) levels were significantly high in the CBA and RFA groups (p < 0.001 for all). TnI elevation (DTnI) was correlated with age (p = 0.033) and median temperature reached during ablation (p < 0.005) in the CBA group, while it was correlated with application time in the RFA group (p < 0.001). Multivariate analysis in the CBA group revealed age and left atrium diameter as positive independent predictors (p = 0.029 and p = 0.046), and DTnI as a negative independent predictor for AF recurrence (p = 0.001). Elevated cardiac biomarkers were not associated with AF recurrence in the RFA group (p > 0.05). Conclusions: The levels of all cardiac biomarkers were elevated after CBA and RFA. Elevated TnI levels after CBA were independent negative predictors of AF recurrence. Measurement of TnI levels after CBA may be useful for the prediction of better clinical outcome.
WOS: 000395790600005
PubMed ID: 27221959
Keywords: Catheter Ablation; Atrial Fibrillation; Myocardial Injury Biomarkers